2021
DOI: 10.1190/geo2020-0610.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling viscoacoustic wave propagation using a new spatial variable-order fractional Laplacian wave equation

Abstract: We propose a new time-domain viscoacoustic wave equation for simulating wave propagation in anelastic media. The new wave equation is derived by inserting the complex-valued phase velocity described by the Kjartansson attenuation model into the frequency-wavenumber domain acoustic wave equation. Our wave equation includes one second-order temporal derivative and two spatial variable-order fractional Laplacian operators. The two fractional Laplacian operators describe the phase dispersion and amplitude attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Hence, the crucial kernel of Q ‐RTM is the high‐efficient time‐domain viscoacoustic wave equation with decoupled amplitude loss and phase dispersion terms. However, the majority of current decoupled viscoacoustic wave equations suitable for Q ‐RTM are based on Kjartansson's constant‐ Q model (Chen et al., 2016; Hao & Greenhalgh, 2021; Hao et al., 2022; Kjartansson, 1979; Li et al., 2016; Mao et al., 2023; Mu et al., 2021; Wang et al., 2018, 2020; Yang & Zhu, 2018b; Zhang et al., 2010; Zhu & Harris, 2014). These wave equations need to be solved using the pseudo‐spectral method (PSM) (Carcione, 2010; Chen & Holm, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the crucial kernel of Q ‐RTM is the high‐efficient time‐domain viscoacoustic wave equation with decoupled amplitude loss and phase dispersion terms. However, the majority of current decoupled viscoacoustic wave equations suitable for Q ‐RTM are based on Kjartansson's constant‐ Q model (Chen et al., 2016; Hao & Greenhalgh, 2021; Hao et al., 2022; Kjartansson, 1979; Li et al., 2016; Mao et al., 2023; Mu et al., 2021; Wang et al., 2018, 2020; Yang & Zhu, 2018b; Zhang et al., 2010; Zhu & Harris, 2014). These wave equations need to be solved using the pseudo‐spectral method (PSM) (Carcione, 2010; Chen & Holm, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The space average strategy by only offers reasonable accuracy in the case of a smooth Q model but introduces large simulation errors in the case of a sharp Q variation. Several different approximations have been developed to transform the variable-order fractional Laplacians into constantorder fractional Laplacians Yang and Zhu, 2018;Xing and Zhu, 2019;Mu et al, 2021), which facilitates the FFT simulations, significantly. Although the FFT differentiation achieves a spectral accuracy in space, the tradtional pseudo-spectral (PS) method uses a second-order FD operator to approximate the time derivative, which limits the temporal extrapolation accuracy to second-order.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the proposed 𝑘-space approach is better than the traditional finite difference method in the second-order precision scheme. Mu et al (2021) developed a viscoacoustic wave equation in the time domain to simulate wave propagation in anelastic media. They proposed a new viscoacoustic wave equation inserting the complex-valued phase velocity derived from the Kjartansson attenuation model in the frequency-wavenumber domain in the acoustic wave equation.…”
Section: Introductionmentioning
confidence: 99%